The Effect of Self-Regulated Learning Model Assisted by The Brainly Application on Students' Learning Outcomes in History - Pratiwi, Feby Dewi; Umamah, Nurul; Marjono, Marjono; Sumardi, Sumardi; Hilmiah, Anis Syatul; Prasky Hartono, Fernanda; Zulfikar, Fahcri (History Education, University of Jember, 2024)
This research aims to see whether there is a significant influence with the application of the Self Regulated Learning model assisted by the Brainly application on learning outcomes in history learning. This research uses a quantitative approach with a quasi-experimental design type, then hypothesis testing is carried out using the ANCOVA test (covariance analysis). The population in this study were all class XI students of SMAN Balung for the 2023/2024 academic year. The samples in this research were students in classes XI 7, XI 9, XI 8 and XI 11. Data collection in this research used documentation, observation and questionnaire techniques. This research shows that there is an influence of the Self Regulated Learning learning model assisted by the Brainly application on learning outcomes, showing the results of the ANCOVA test with a significance value of 0.000<0.05 and a partial eta squared value of 0.221 including a large influence in the application of this model. The average score of the control class taught using the Project Based Learning model was 83.278, while the experimental class taught using the Self Regulated Learning model assisted by Brainly had an average score of 85.595. Based on the average score results, it can be seen that the experimental class is superior to the control class. The conclusion that can be drawn from this research is that a significant influence was obtained from the application of the Self Regulated Learning model assisted by the Brainly application on students' learning outcomes in history learning.